Development and Validation of Cognitive Rehearsal as a Training Strategy for Arthroscopic Surgery. Issue 7 (18th July 2016) - Kovacevic, David; Hodgins, Justin Lane; Lowe, Dylan T.; He, Janice; Popkin, Charles Aaron; Lynch, Thomas Sean; Ahmad, Christopher S.
Objectives: Surgical performance is a highly intellectual activity that involves the processing of perceptual information from the five senses. Strategies to process, organize, and retain this perceptual information may benefit learning techniques. Once such strategy, cognitive rehearsal, is the activity where a skill is rehearsed in memory prior to the actual performance. This study aimed to develop and validate a cognitive rehearsal strategy for arthroscopic knee surgery in orthopaedic residents. We hypothesized that this training tool will lead to increased comfort and confidence with arthroscopic surgery performance. Methods: An expert surgeon was filmed performing an arthroscopic ACL reconstruction using patellar bone-tendon-bone autograft. An instructional training video was then created incorporating the extracorporeal and arthroscopic footage with voice over and subtitles. Following the surgery, cognitive recall of the procedure was conducted with the surgeon to identify key visual, cognitive, and kinesthetic cues to develop a mental imagery script to enhance rehearsal of arthroscopic surgery. Orthopaedic residents from two academic training programs were invited to participate. Demographic information including training level, previous musical experience, organized sports participation, and preferred learning style was collected. The training session consisted of a relaxation exercise, instructional video of an expert performing the procedure, learning the mental imagery script, and rehearsing the procedure out loud with a partner. The residents' ability to rehearse the procedure was assessed before and after the training session with a modified version of a previously validated questionnaire, and a post-training session survey was administered to define which components of the rehearsal seemed most beneficial. Statistical analysis included a reliability analysis for internal consistency, and a nonparametric Wilcoxon test to compare the composite cognitive rehearsal scores of the junior and senior residents. A nonparametric Mann-Whitney test was used to evaluate performance of each group before and after the training session on each item of the questionnaire. Results: 53 of 62 (85%) residents completed the demographics survey prior to the training session, while 44 of 62 (71%) residents were available to complete the training exercise. A Cronbach alpha of 0.9494 for the pre-training (n=44) and 0.9394 (n=44) for the post-training suggested that the cognitive rehearsal questionnaire was internally consistent, allowing for the reliable summation of individual items to a composite score. The median composite cognitive rehearsal scores of the junior residents significantly improved from 24 pre- to 42 post-training exercise (p = 0.002). Senior resident median composite scores improved after training from 38 pre- to 46 post-exercise (p = 0.041). Those with previous musical training and kinetic / visual learners performed better during the training session. Both groups found the entire process valuable. Conclusion: This is the first study to develop and validate cognitive rehearsal as a low cost, high touch training strategy for arthroscopic surgery in orthopaedic residents. Cognitive rehearsal holds promise as a training tool for mastery of executive routine, performance quality, and increasing knowledge, comfort, and confidence for both junior and senior residents learning arthroscopic surgery.